Desain Penampang Sungai Way Besai Melalui Peningkatan Kapasitas Sungai Menggunakan Softwere HEC-RAS - Utami, Tri; Purwadi, Ofik Taufik; Susilo, Gatot Eko (Universitas Lampung, 2016)
Way Besai river is located in Sumberjaya subdistrict, West Lampung district, Lampung. It is one of the sub river from Tulang Bawang river. Way Besai river has been used as a the electric power source, known as Besai hydropower. Besai Hydropower has decreased energy supply of 40 MW from the supply optimum can reachs 90 MW. his is due to the catcment area conditions of the Way Besai rivers are